Fundamentals of Entrepreneurship ENT 300 : Sidik Ahh Dessert By De' Ruin / Nur Farhana Izzati Ahmad Shahlan ... [et al.] - Ahmad Shahlan, Nur Farhana Izzati; Sarbini, Noorul Izzawana; Abdul Rahman, Nur Fatihah; Bosco, Steven Luca; Ahat, Peter Vyner (2019)
Our company’s name is Sidik Ahh Dessert by De Ruin. We use ‘Sidik Ahh’ because the dessert that we made is delicious. We serve dessert that is originally from Thailand. It is a type of dessert that customer craving for. Besides, we operate our business using a food carts to deliver customer’s satisfaction. This company consists of five members. This company establish on 2019. Each member has their own position as General, Marketing, Administration, Operational and Financial Manager. Our target markets are wholly Bintulu. Our company operates from 2.00 p.m. until 7.00 p.m. at Tanjung Batu Beach every day except on Wednesday. We use cash as exchange of services and products that we provide. The company name, Sidik Ahh Dessert by De’ Ruin as we suggested and decided to name it because is unique. Sidik Ahh means delicious in Bidayuh. Our business entity of the company is a Partnership. We will ensure that our customer will own our product and we will serve them right due to satisfaction of our customer. It is because our customer is our first priority. Since this food carts business is less competitors, we will try our best to push full effort to become the best food cart in Malaysia and try to be well-known in Malaysia.